Analisis Implementasi Pembelajaran Matematika Abad 21 untuk Siswa Madrasah di Era Industri 4.0 - Irawan, Adi; Rohmah, Zulfiani; Rusmayadi, Muh. (LP2M STAI Darul Kamal NW Kembang Kerang, 2025)
This study aims to determine the application of 21st-century skills in madrasas in mathematics learning and the implementation of 21st-century skills in mathematics learning to help madrasah students face the challenges of the Industrial Revolution 4.0 and to determine the factors that support and hinder the implementation of 21st-century learning in madrasas. This study uses a descriptive qualitative approach. Research data were collected through in-depth interviews, observations, and document analysis such as lesson plans, learning media, syllabi, and student evaluation results. The results show that mathematics learning in madrasas is currently only in the initial stage of implementing 21st-century skills. Mathematics learning that integrates 21st-century skills not only improves academic achievement but also helps build students' character and ability to adapt to an ever-changing world. 21st-century mathematics learning in madrasas still faces many challenges such as conventional approaches, limited teacher competencies, and inadequate infrastructure.